Actual changes in the legal regulation of relations of subsoil use in Russia - А М Volkov (RUDN Journal of Law, 2012)
Article is devoted actual changes of the legislation in the field of subsoil use in Russia in 2011, come into force and having special value for for users of subsoil in 2012г., offers on legislation perfection in this sphere are stated.